SISTEM MONITORING CUACA PADA LAHAN PERTANIAN BERBASIS IoT - Julianto, Diki; Sollu, Tan Suryani; Alamsyah, Alamsyah; Mustari, Aidynal; Martdiansyah, Martdiansyah (Foristek, 2025)
Weather is information that is very necessary, especially on agricultural land, to support plant growth, productivity, and yield. Weather monitoring currently still uses a manual system, so it requires quite a lot of time and energy. Apart from that, manual monitoring also allows limited types of data that can be measured directly by humans. The weather monitoring system design is based on the parameters used, namely temperature, humidity, wind speed, light intensity, and rain conditions, using the LoRa module, which can be accessed online and offline and in real- time on the website and LCD.The test results show that the system can work well with the parameters used, namely temperature, with an average error value of 1.81% and an accuracy of 98.19%; humidity, with an average error value of 0.675 and an accuracy of 99.325%; and average wind speed. The error value is 1.83% with an accuracy of 98.17%, the average light intensity error value is 2.42% with an accuracy of 97.58%, and the rainy conditions are successful in providing information whether it is raining or not.